From Where to Where – Running Away from Care. (14th April 2015) - Jackson, Annette
<x content-type="archive" xml:space="preserve">Abstract</x> This opinion piece draws on the literature regarding absconding from care and its links with child sexual exploitation and trauma. The author draws on her experience in the child protection, out-of-home care and therapeutic services to raise some questions and suggest some themes about how the system responds when young people run away from what is purportedly safe to what is palpably unsafe. The article concludes with a brief description of trauma-informed practice and suggests that this concept is a useful contribution in our response to helping young people no longer needing to run.